Randomize IPv6 Stateless Address Autoconfiguration in None-stable Storage Arduino Devices - Zolidah Kasiran; Rizaki Napi (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
The pervasiveness of IoT device requires each device to have a unique address number in order to communicate. Internet Standard specified in RFC4941-Privacy Extension for SLAAC had question raised on the randomness of the IPv6 address generated due to the shortcoming of device random generator algorithm. Improvements to the RFC’s have been proposed and Arduino Uno had been selected as IoT platform since it currently supports IPv6 implementation. An enhancement algorithm was developed. The generated IPv6 address is then tested against ENT Random Test tool for observation and conclusion.